(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
War Powers in British Law: The Historical Evolution of the War Prerogative between Monarch, Cabinet, and Parliament This essay aims to highlight, particularly by retracing the ways in which the English (and subsequently British) monarchy has exercised military power throughout its centuries-long history, the transformation undergone by the "war prerogative", like other royal prerogatives, through shifts in institutional balances and the stratification of constitutional conventions. Currently, the decision to deploy armed forces in situations of armed conflict is a prerogative power, exercised by government ministers. Constitutional conventions require the Prime Minister to authorize the use of British forces in military action on behalf of the Crown. Decisions regarding military action are made within the Cabinet. Constitutionally, Parliament has no legally established role in decisions to deploy armed forces, and the Government has no legal obligation to consult or keep Parliament informed, but recently a new convention has also allowed the House of Commons to express its opinion on military interventions in advance.